The second Born approximation in theory of bremsstrahlung of relativistic electrons and positrons in crystal - Shul’ga, N.F.; Syshchenko, V.V. (Вопросы атомной науки и техники, 2001)
The formulae for the cross section of bremsstrahlung by relativistic electrons and positrons taking into account the contribution of the second Born approximation are obtained. The dependence of the radiation cross section in the field of atomic plane on the sign of charge of the particle is considered.